Educational Disadvantage and University Entrance for Pakistani and Nepalese School Students in Hong Kong: The Possibilities of Legal Redress - Khattak, Shahmim Khan (2025)
This thesis focuses on how Pakistani and Nepalese school students in Hong Kong are educationally disadvantaged compared to local Chinese students by a combination of experiencing difficulties learning Chinese and the entrance policies of universities. The research was undertaken from a legal perspective to explore the possibilities of legal redress, which is one important way of addressing these inequalities. The research involved interviews with stakeholders, developing a comparative case study and, finally, exploring the legal case. Ethnic minority groups in Hong Kong account for 8 % of the total population. The Hong Kong Special Administrative Region Government is under an obligation to guarantee equal access to education to all students without discrimination. However, there is evidence from policy documents and scholarly literature that ethnic minority students are not supported to learn and qualify in Cantonese to a high enough level to afford them equal access to one of the nine prestigious JUPAS universities. The universities’ admissions procedures appear to be discriminatory by placing a high value on proficiency in Chinese, even when not necessary for university study. The thesis explores the policy and legal background to the problem and then takes three methodological approaches to taking the investigation further. First, to explore how those affected perceive and experience the problem, 16 interviews were undertaken with 8 students from ethnic minority groups, 6 principals and 2 teachers of schools with a large number of ethnic minority students. These interviews revealed that students do experience educational disadvantage in relation to university entrance, but that they are often unaware of it. Despite efforts, it was eventually too difficult to gain any responses from universities about their admission policies and procedures. Secondly, it compares the education system and policies of Hong Kong with Singapore which is composed of three major ethnic student groups. The comparison shows that the situation in Hong Kong is not inevitable: Singaporean government maintains greater equality and fairness between the groups than in Hong Kong. Thirdly, it undertakes a thorough legal analysis using precedents and cases. Taking all the evidence together, the thesis concludes by confirming that an aggrieved member of the ethnic minority students could seek legal redress or remedies against one of the nine universities under Judicial Review on the basis of the Race Discrimination Ordinance and/or any other statutes on constitutional laws or through any statutory bodies such as the Equal Opportunities Commission or the Legal Aid Department.